Distribution and Function of Neuropeptides W/B Signaling System - Chottova Dvorakova, Magdalena (Frontiers in Physiology, 2018)
Neuropeptide W (NPW) and neuropeptide B (NPB) are two structurally and functionally related regulatory peptides, which are highly expressed in several brain regions and, additionally, in some peripheral tissues. Nevertheless, their distributions in the tissues are not similar. They act on target tissues via two subtypes of G protein-coupled receptors which are designated as NPBWR1 (GPR7) and NPBWR2 (GPR8), respectively, and possess different binding affinities. NPB activates NPBWR1, whereas NPW stimulates both the receptors with similar potency. Both of these peptides takes a part in the central regulation of neuroendocrine axes, feeding behavior, energy homeostasis, cardiovascular functions, circadian rhythm, pain sensation, modulation of inflammatory pain, and emotions. Over the past few years, studies have shown that NPB is also involved in sleep regulation. On the contrary, NPW participates in regulation of vascular myogenic tone, inhibits gastric tension sensitive vagal afferents and insulin secretion. Also, expression of NPW in the stomach is regulated by feeding. Abovementioned findings clearly demonstrate the functional diversity among NPW versus NPB signaling systems. In this review, signal transduction pathways of NPW/NPB are critically evaluated and observed together with mapping of expression of their signaling systems.